2022
DOI: 10.1097/sap.0000000000003315
|View full text |Cite
|
Sign up to set email alerts
|

Lesion Site Is the Key Prognostic Factor for Keloid Patients Receiving Surgery With Adjuvant Radiotherapy

Abstract: BackgroundKeloid is a benign tumor with high recurrence rate; accordingly, complete surgical excision with adjuvant radiotherapy is one of the most effective treatments. This study reviewed outcomes of keloid patients receiving surgery and adjuvant radiotherapy in Kaohsiung Medical University Hospital.Materials and MethodsAll patients received radiation dose with 15 Gy, with their first radiotherapy within 24 hours after surgical excision. The end points were recurrence rate and local recurrence-free interval … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 25 publications
(69 reference statements)
2
3
0
Order By: Relevance
“…The keloid located on chest had the highest recurrence rate, while keloid located on ear had lowest recurrence rate. Similar results were also reported by other study [ 22 ]. The prescription BED was similar to other studies, and also achieved a satisfactory effect.…”
Section: Discussionsupporting
confidence: 93%
“…The keloid located on chest had the highest recurrence rate, while keloid located on ear had lowest recurrence rate. Similar results were also reported by other study [ 22 ]. The prescription BED was similar to other studies, and also achieved a satisfactory effect.…”
Section: Discussionsupporting
confidence: 93%
“…13 This induces the augmentation of inflammatory cells and growth factors such as macrophages, mast cells, neutrophils, lymphocytes, and vascular endothelial growth factor (VEGF), inducing cell proliferation, angiogenesis, and collagen synthesis. 16 In this study, moderate and severe inflammatory infiltrates were observed more at the edge of the lesion (chest, shoulders, and ears) than in the center of the lesion, which is in accordance with the Jiao et al study reporting moderate perivascular chronic inflammatory infiltrates in all keloids. 21 Another study described increased inflammation at the edge of the lesion, which then gradually declined, toward the center of the lesion.…”
Section: Discussionsupporting
confidence: 92%
“…17 The predilection site of keloid is a hightension area, such as the chest, back, and shoulders. 16 We also found that keloids were predominantly observed on the chest. This finding is in accordance with the Huang et al study in 2020, in which keloids were dominantly seen on the chest, the high-tension area.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…If divided into two groups of locations containing cartilage and not containing cartilage, the rates are 58.07% and 41.93%, respectively. This rates are also quite variable in the studies of other authors in the world: Tae Hwan Park studied 842 keloids with 77.08% cartilage-free keloids, Bernardo Hochman also recorded the same results with Park with 82% of keloids at the cartilage-free position; in the study in Thailand with 43 auricular keloids, the position containing cartilage also accounted for 67.4% (11). Because the formation of keloids is affected by various factors, there seems to be no rule as to which location the keloid is more dominant.…”
Section: Locationmentioning
confidence: 88%